Chinese Aid in Africa: Attitudes and Conflict - Sulin Sardoschau; Alexandra Jarotschkin (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
This study examines Chinese aid projects' impact on conflict and perceptions of China in 820 African districts from 2000 to 2012. We show that a 10% increase in Chinese aid projects results in a 6% increase in conflict incidents. This rise is mainly due to confrontations involving non-state actors, such as militias and rebel groups, and clashes between these groups and government forces. Civilian attitudes toward China's presence do not drive this increase, as evidenced by both revealed and stated preferences. We find that Chinese aid does not provoke protests, riots, or strikes, nor does it amplify critical views among Africans regarding Chinese culture, resource extraction, or land acquisitions. Our evidence suggests that Africans attribute the rise in conflict to the interaction of resource influx and local politics, rather than to China itself, reflecting a discerning perspective on China's influence on the continent.
Keywords: 330